Factors influence self-care behavior and diabetic management in patients with diabetes mellitus - Sekardiani, Ni Luh Putu; Swarjana, I Ketut; Satriani, Ni Luh Adi; Megayanti, Sri Dewi (MEDISAINS, 2023)
Background: Self-care behavior and diabetic management in patients with diabetes mellitus (DM) tends to be low, especially during the COVID-19 pandemic. Various studies have found the influence of knowledge with self-care behavior diabetic management, as well as attitudes, motivation, family support and self-efficacy, but research analyzing the most dominant factors that play a role in influencing diabetic patients in self-care behavior and diabetic management is still limited.Purposes: Analyzing the factors that influence self-care behavior and diabetic management in diabetic patients. This study also analyzes the factor that play the most dominant role to influence self-care behavior and diabetic management in diabetic patients.Methods: This type of research is observational analytic with cross-sectional design. Patients of type 2 diabetes were the population in this study, with a sample size of 312 selected by convenience sampling. Factors of knowledge, attitude, motivation, family support and self-efficacy were observed in the study which were thought to be factors affecting self-care behavior diabetic management. The data were analyzed by chi square test and logistic regression.Results: The factors of knowledge, family support, and motivation significantly influence self-care behavior and diabetic management (p<0.05). The motivation factor is the most dominant factor affecting it (AOR 2.760; p<0.001).Conclusion: Good knowledge about diabetes management plus optimal family support and high motivation will improve self-care behavior and diabetic management in diabetic patients.